2015
DOI: 10.1016/j.bone.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Bone's responses to mechanical loading are impaired in type 1 diabetes

Abstract: Diabetes adversely impacts many organ systems including the skeleton. Clinical trials have revealed a startling elevation in fracture risk in diabetic patients. Bone fractures can be life threatening: nearly 1 in 6 hip fracture patients die within one year. Because physical exercise is proven to improve bone properties and reduce fracture risk in non-diabetic subjects, we tested its efficacy in type 1 diabetes. We hypothesized that diabetic bone's response to anabolic mechanical loading would be attenuated, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 68 publications
6
35
0
1
Order By: Relevance
“…Clinical findings in pediatric populations suggest insulin resistance to precede bone maturation [18] and impair muscle-bone unit development [16]. This is supported by recent animal data showing that hyperglycemia reduces responses to mechanical loading [33]. …”
Section: Discussionmentioning
confidence: 96%
“…Clinical findings in pediatric populations suggest insulin resistance to precede bone maturation [18] and impair muscle-bone unit development [16]. This is supported by recent animal data showing that hyperglycemia reduces responses to mechanical loading [33]. …”
Section: Discussionmentioning
confidence: 96%
“…showed that exposure to high glucose reduced flow‐induced PGE 2 release (Fig. ) and soluble RANKL secretion from osteocytes, and altered regulation of osteocyte apoptosis in response to mechanical stimulation . Considerable reduction of load‐induced anabolic response in ulnae of adult Akita mice was also observed .…”
Section: Are Diabetic Bones “Deaf” To Mechanical Loading?mentioning
confidence: 88%
“…The impact of T1D on bone response to mechanical loading had been investigated, both in vivo and in vitro [88]. Male Akita mice, a model of severe insulin-deficiency diabetes, demonstrate impaired bone formation in response to repetitive mechanical loading of the ulna, when compared to wild-type mice or to female Akita mice (a model of milder blood glucose elevation) [88].…”
Section: Effects Of Type 1 Diabetes On Osteocytesmentioning
confidence: 99%
“…The impact of T1D on bone response to mechanical loading had been investigated, both in vivo and in vitro [88]. Male Akita mice, a model of severe insulin-deficiency diabetes, demonstrate impaired bone formation in response to repetitive mechanical loading of the ulna, when compared to wild-type mice or to female Akita mice (a model of milder blood glucose elevation) [88]. Consistent with these findings, exposure of MLO-Y4 osteocytes to hyperglycemic culture conditions has been shown to: 1) impair the osteocyte mechanosignaling response to oscillatory fluid shear stress [88, 89]; and to 2) attenuate the expected activation of anti-apoptotic pathways [88].…”
Section: Effects Of Type 1 Diabetes On Osteocytesmentioning
confidence: 99%